Formation of a Surface Charged Microarc Coatings Modified by Boehmite Nanoparticles; Key Engineering Materials; Vol. 769 : High Technology: Research and Applications (HTRA 2017) - Chebodaeva V. V. Valentina Vadimovna; Sedelnikova M. B. Mariya Borisovna; Golohvast K. S. Kirill; Zaharenko A. Aleksandr; Sharkeev Yu. P. Yury Petrovich (2018, 2018)
Title screen